PENGARUH PROGRAM SWASEMBADA BERAS TERHADAP PERUBAHAN FUNGSI KELUARGA PETANI DI DESA TOPANG KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - Naviah, Lailin; ", M. Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in Desa Topang Kecamatan Rangsang KabupatenKepulauan Meranti. The purpose of this research is to determine the factors thataffect the farming communities participate execute Program Swasembada Berasand to analyze changes the function of farm families with a 100 % head of thefamily at home. This research entitled “Effect of Program Swasembada Berasagainst Change Function Family Farmers In Desa Topang KecamatanRangsang Kabupaten Kepulauan Meranti”. The focus topic of this research iswhat factors are affect the farming communities participate execute ProgramSwasembada Beras and any changes happened to farmer family functions with a100 % head of the family at home. Population and sample in this study populationare farmers participate execute Program Swasembada Beras in Desa Topang 300heads of families. And contain of samples taken 10 % of the farming communitiesparticipate execute Program Swasembada Beras as many as 30 heads of families.Writer used quantitative descriptive the analysis seeks to provide a detailedoverview is based on the fact that there are in the field. Data instruments areobservation and interview. Result show that the dominant factors are affect thefarming communities participate execute Program Swasembada Beras areinternal factor (the actors wants to participate) and exsternal factors; economysuch as low levels of income, socio-cultural and the knowledge factor. Thedominant perception is changes in family functioning is the farmers is economicfunctions that meet the needs of the family, affective function is to provideaffection and attention, whereas socialization functions that provide education inthe family, and protection functions, namely to provide protection, control andcare in the family.Key words: Program Swasembada Beras, Community Farmer, FamilyFunction